(untitled) (Olhares, 2025)
With this study I seek ways that indicate modes of affiliation between Dionysian attributes and the permanence of this god in the sphere of theater in the polis. Why consider theater as a gift from Bacchus, like wine, death, rebirth and ecstasy? Starting from the qualities of this deity and its connections with the origins of Western theater, I am interested in evidence of Dionysus’ primordial characteristics that may still prevail in theatrical practice. I intend to address this issue here, sharing a reflection on the Dionysian aspects in ancient Greek theater, its origins and development in the polis.